Screening of concurrent alpha-Thalassaemia 1 in beta-Thalassaemia carriers - Chong, Y.M.; Tan, J.; Zubaidah, Z.; Rahimah, A.; Kuldip, K.; George, E. (Malaysian Medical Association, 2006)
Thalassaemia is an inherited blood disorder and is a significant public health problem in Malaysia, with many not knowing they carry gene for thalassaemia. The two major forms are alpha and beta thalassaemia. An individual can co-inherit both the alpha and beta thalassaemia genes. This study determined the frequency of cincurrent carriers of alpha thalassaemia in 231 beta thalassaemia carriers. Gap-PCR was done on extracted DNA of the beta thalassaemia samples to check for alpha thalassaemia 1 molecular defect. Eight (3.5) samples were found to have concurrently inherited the alpha thalassaemia 1 deletion. The significant carrier rare for alpha thalassaemia 1 indicates the need for the implementation of DNA analysis to complement thalassaemia screening in high risk populations.